(untitled) (Prosiding dan Call Paper Widya Wiwaha, 2024)
This study aims to determine the effect of financial knowledge and financial attitudes on the financial management behavior of students in the Accounting Department, Faculty of Economics and Business University of Mataram with personality as a moderating variable. Data collection was done by distributing questionnaires to 88 students included in the research sample. The sampling technique used proportional random sampling. The results of the study showed that financial knowledge and financial attitudes had a significant effect on students financial management behavior, both partially and simultaneously. Meanwhile, the results of the moderation regression analysis found that personality could not moderate financial knowledge or financial attitudes towards students’ financial management behavior. This study is expected to be a source of reference in managing finances for the community and especially for students in everyday life.